Measuring services quality of bus transportation in Universiti Utara Malaysia (UUM) - Hassim, Wan Mohd Rozlee; Abdullah, Mohd Nabil Maula; Daud, Ali-Bashi Musse; Zainuddin, Nizamuddin (2017)
This study aims to measure service quality of bus transportation in Universiti Utara Malaysia (UUM).Our group decided to choose this topic because bus transportation plays as an important function in terms of transportation in moving students around campus in UUM.To measure service quality in our topic, we will focus on the relationship between service quality of bus transportation and three aspects that we retrieved and developed from SERVQUAL (Service Quality) theory dimension by Parasuraman which are tangible, reliability, and responsiveness. Our population and sample for this study that we will use is amongst undergraduate students in Universiti Utara Malaysia.Our population for this study is about 14000 students and we will take sample about 400 of them.During conducting this study, we use questionnaires as our main instrument for collecting data from the study population.The student population is significant to their responses because they are the customers and have knowledge in the particular services. Data were analyzed by using reliability analysis, correlation analysis, and linear regression analysis for measuring service quality of bus transportation in Universiti Utara Malaysia. Based on the analysis, it was found that all three independent variables are acceptable and significant towards our dependent variable in this study.The survey regarding this study was constrained by the sample size and cross-section due to the time constraints.Last but not least, this research is significant because it will contribute to the actual current level of service quality of bus transportation in Universiti Utara Malaysia.Next, the bus management can improve their service quality level of bus transportation, address problem occurred regarding the services that they have delivered, and also overcome the problem with rapid solutions during a specific time period.